Role of Human Computer Interaction - et.al, Mohit Dhiran, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Human Computer Interaction (HCI) as the name suggests is referred to as the interaction between the user and the machine(computer). As all of us are surrounded by the computers so it is important to know and study about how human computer interaction has been possible and how it has developed a major field in Computer Science. Human computer interaction is a multidisciplinary field which involves theories and practices from numerous field which include computer science, psychology and cognitive science, sociology and anthropology, ergonomics being some of them. Every element is accounted in HCI from their perception and the world interaction to the long history of using computers and technology. Poor designing can create unanticipated problems. This paper provides an overview regarding human computer interaction how it has evolved over the years and the role it is played in the field of computer science.